2016
DOI: 10.1080/15022250.2016.1262514
|View full text |Cite
|
Sign up to set email alerts
|

Networking and collaboration between tourism and agriculture: food tourism experiences along the National Tourist Routes of Norway

Abstract: Food and culinary routes have been embraced by many destinations (Hjalager & Corigliano, 2000). However, these routes often include narrow geographical areas. The purpose of this study was to identify the challenges and possibilities of networking and collaboration in a food tourism project in a larger geographic area, specifically the Taste of National Tourist Routes (TNTR) in Norway. Although contacts among business operators and participants have been established, different priorities and dissatisfaction am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Direct contact with the producer adds value to the local products and give a personal touch. Through routes the tourism offer is expanded with new products, activities, and destinations [9].…”
Section: Tourism Routes For the Diversification Of Rural Livelihoods mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct contact with the producer adds value to the local products and give a personal touch. Through routes the tourism offer is expanded with new products, activities, and destinations [9].…”
Section: Tourism Routes For the Diversification Of Rural Livelihoods mentioning
confidence: 99%
“…Through the configuration and structuring of resources and services, they can constitute an experience that takes into account the motivations interests expectations and perceptions of visitors. For the local population, routes can mean the diversification of their livelihoods, particularly when they are structured in a way that seeks to maximise the potential benefits for the local community [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…They found that tourists acquired new tastes during their vacations, eating local foodstuff and assisting in the growth of local agriculture. Mei et al, 2016 have studied the collaboration between tourism and agriculture in Norway. The authors stated that building relationships and sharing knowledge between tourist enterprises and foodstuff producers remains difficult.…”
Section: Agriculture and Tourism Linkagesmentioning
confidence: 99%
“…If the pluralism of logic is too obvious and there is a lack of dynamism in actors' behavior (willingness to compromise), initiatives need to undergo significant organizational changes or they fall apart. The success of the food experience thus depends significantly on the compatibility of the actor's motives because this determines their ability to positively collaborate within the network (Mei, Lerfald and Brata 2017).…”
Section: Introductionmentioning
confidence: 99%